2023
DOI: 10.3389/fpubh.2023.1209809
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of patients with type 2 diabetes based on medication adherence data

Abstract: IntroductionType 2 diabetes mellitus (T2DM) is a complex, chronic disease affecting multiple organs with varying symptoms and comorbidities. Profiling patients helps identify those with unfavorable disease progression, allowing for tailored therapy and addressing special needs. This study aims to uncover different T2DM profiles based on medication intake records and laboratory measurements, with a focus on how individuals with diabetes move through disease phases.MethodsWe use medical records from databases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Recent research showed that the onset of long COVID could be associated with metabolic dysfunction [23][24][25]. A study performed in the same region reports that metformin is often the first line of treatment for diabetes patients [26]. Metformin has been shown to have a potential protective role in COVID-19 [27] and long COVID [28,29] so it might be the contributing factor for the shorter duration of PCS among diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research showed that the onset of long COVID could be associated with metabolic dysfunction [23][24][25]. A study performed in the same region reports that metformin is often the first line of treatment for diabetes patients [26]. Metformin has been shown to have a potential protective role in COVID-19 [27] and long COVID [28,29] so it might be the contributing factor for the shorter duration of PCS among diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this section, we look at the various AI algorithms that are used when dealing with this kind of data. Markovic et al [32] applied a Novel NLP to medical records to create a patient-specific drug profile for diabetic patients.…”
Section: A Ai Techniques and Healthcarementioning
confidence: 99%
“…It could also enable patient empowerment by allowing them to play an active role in the management of their disease ( 11 ). eHealth also has a positive impact on medication adherence ( 12 ) and in the management of polypharmacy ( 13 ), which is a major challenge among patients with chronic diseases like diabetes ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%